Electro-synthesis and characterization of TiO2 nanoparticles and their application in removal of congo red from water without UV radiation. Issue 5 (1st April 2018) - Kardanzadeh, Maryam; Kazeminezhad, Iraj; Mosivand, Saba
Abstract: TiO2 nanoparticles were synthesized using electro-oxidation method, for the first time. The synthesis was carried out using the electro-oxidation of titanium sheet in the presence of an amine in an electrochemical cell. The amine acts as supporting electrolyte and electrostatic stabilizer. The effect of applied voltage, stabilizer concentration, electrolyte temperature and annealing temperature on morphology and structural properties of the products were investigated. The samples were characterized using XRD, FT-IR, FE-SEM, and UV–visible spectroscopy. XRD results confirmed the phase transition from amorphous to anatase and rutile phase by annealing at 700 °C and 900 °C, respectively. FT-IR results confirmed the products were covered by the surfactant molecules before the annealing process. FE-SEM images showed that the mean particle size ranges from 14 nm to 40 nm, depending on the growth conditions. The ability of electro-synthesized TiO2 nanoparticles on removal of congo red from water has been investigated. The best advantage of TiO2 nanoparticles produced with electro-oxidation method is that it is possible to remove the color from water without UV radiation. The result showed that at pH of 5, after 110 min stirring time, the dye concentration is significantly reduced.